Tác động của hệ thống kế toán quản trị và kiểm soát đến kết quả hoạt động kinh doanh của doanh nghiệp: Vai trò của đổi mới sáng tạo mở hướng nội - Trần Thị, Quanh; Lê Đình, Trực; Phạm Ngọc, Toàn (JOURNAL OF ASIAN BUSINESS AND ECONOMIC STUDIES, 2026)
This study examines the impact of management accounting and control systems on inbound open innovation and firm performance, while also testing the mediating role of inbound open innovation. Analysis of data from 262 medium and large enterprises in Vietnam using SmartPLS4 software shows that the use of both diagnostic and interactive management accounting and control systems positively influences inbound open innovation. Furthermore, it affects firm performance through inbound open innovation. This study contributes to the academic literature on the use of the management accounting system combined with the levers of control framework by Simons (1995) in the context of open innovation. In addition, the article provides important managerial implications for managers in using management accounting and control systems and actively acquiring external knowledge and technology to improve firm performance.
Keywords: Management accounting; Open innovation; Firm performance